LiBCO / Noryana Ahmad Khusaini ... [et al.] - Ahmad Khusaini, Noryana; Nasrudin, Nur Hasni; Daud, Mohd Shamsul; Abd Rahman, Noraini; Ahmad Junid, Rosida; Ibrahim, Siti Fairuz (2021)
LiBCO stands for Library Portal for Community Outreach. It is an integrated online platform for Malaysian libraries to disseminate and deliver their outreach program activities to public at home. This system was developed in 2019 by a group of researchers in the fields of Information Management, Computer Science, Industrial Design, and the English Language in collaboration with a librarian from Perbadanan Perpustakaan Awam Negeri Kedah. This system was awarded a gold medal at the INDELIB competition in 2019. This system is also copyrighted by MYIPO. For this competition, we bring the LiBCO 2.0 with the new improved features to meet a new target audience which is B40 students with special needs from Sekolah Menengah Pendidikan Khas Vokasional (SMPKV) Merbok to receive outreach program activities that has been customized for them through LiBCO especially during the Covid-19 pandemic and MCO. In terms of novelty, it is a unique system that is not yet available on the market. Therefore, it has the potential to be commercialized. The marketing developer team is ready to assist, design and develop the system if there is a request from any stakeholder interested in purchasing the system. A consultancy service will also be provided which may trigger marketing potential. As for the usability of the system, the content of the system is useful and is developed based on the STIE national niche domain for education which focuses on personalized and experiential learning, micro credentials, and global online learning: promoting local content. The effects of the implementation of the system were mapped on a national STIE niche area that is expected to improve social well-being, the dual impact enabler (economic and societal) and the economic booster.